Effect of super-chilled preservation on the water-holding properties of fresh beef during storage - WEN, Yongping; LIU, Dayu; LLIU, Yang; LIU, Lijia; WANG, Xinhui (Food Science and Technology, 2023)
In this study, comparison of the effects of chilled (4 °C), super-chilled (-4 °C), and frozen (-18 °C) storage on the water-holding properties was evaluated by drip loss, surface hydrophobicity, and calpain activity of raw beef. These results indicated that storage temperature can significantly affect the water-holding properties. In contrast to chilled storage, super-chilled storage can maintain a higher thiol group content, which can maintain better myofibrillar protein hydration capacity. Furthermore, super-chilled storage effectively slowed down the increase in the rate of protein hydrophobicity compared with chilled and frozen storage. Additionally, the super-chilled sample exhibited the highest glutathione reductase activity, followed by the frozen sample. These results revealed that super-chilled storage is a good way to preserve the water-holding properties of raw beef.